## C4 - Homogeneous second-order linear ODE (ver. 1)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 2)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 3)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 4)

Find the general solution to the given ODE.

$y''+8y'+16y = 0$

$y= k_{1} t e^{\left(-4 \, t\right)} + k_{2} e^{\left(-4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 5)

Find the general solution to the given ODE.

$y''-2y'+y = 0$

$y= k_{1} t e^{t} + k_{2} e^{t}$

## C4 - Homogeneous second-order linear ODE (ver. 6)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 7)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 8)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 9)

Find the general solution to the given ODE.

$y''+8y'+16y = 0$

$y= k_{1} t e^{\left(-4 \, t\right)} + k_{2} e^{\left(-4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 10)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 11)

Find the general solution to the given ODE.

$y''+6y'+9y = 0$

$y= k_{1} t e^{\left(-3 \, t\right)} + k_{2} e^{\left(-3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 12)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 13)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 14)

Find the general solution to the given ODE.

$y''+2y'+y = 0$

$y= k_{1} t e^{\left(-t\right)} + k_{2} e^{\left(-t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 15)

Find the general solution to the given ODE.

$y''-8y'+16y = 0$

$y= k_{1} t e^{\left(4 \, t\right)} + k_{2} e^{\left(4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 16)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 17)

Find the general solution to the given ODE.

$y''+6y'+9y = 0$

$y= k_{1} t e^{\left(-3 \, t\right)} + k_{2} e^{\left(-3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 18)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 19)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 20)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 21)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 22)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 23)

Find the general solution to the given ODE.

$y''+2y'+y = 0$

$y= k_{1} t e^{\left(-t\right)} + k_{2} e^{\left(-t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 24)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 25)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 26)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 27)

Find the general solution to the given ODE.

$y''-2y'+y = 0$

$y= k_{1} t e^{t} + k_{2} e^{t}$

## C4 - Homogeneous second-order linear ODE (ver. 28)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 29)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 30)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 31)

Find the general solution to the given ODE.

$y''-2y'+y = 0$

$y= k_{1} t e^{t} + k_{2} e^{t}$

## C4 - Homogeneous second-order linear ODE (ver. 32)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 33)

Find the general solution to the given ODE.

$y''+2y'+y = 0$

$y= k_{1} t e^{\left(-t\right)} + k_{2} e^{\left(-t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 34)

Find the general solution to the given ODE.

$y''-8y'+16y = 0$

$y= k_{1} t e^{\left(4 \, t\right)} + k_{2} e^{\left(4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 35)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 36)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 37)

Find the general solution to the given ODE.

$y''-8y'+16y = 0$

$y= k_{1} t e^{\left(4 \, t\right)} + k_{2} e^{\left(4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 38)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 39)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 40)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 41)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 42)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 43)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 44)

Find the general solution to the given ODE.

$y''+2y'+y = 0$

$y= k_{1} t e^{\left(-t\right)} + k_{2} e^{\left(-t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 45)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 46)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 47)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 48)

Find the general solution to the given ODE.

$y''-2y'+y = 0$

$y= k_{1} t e^{t} + k_{2} e^{t}$

## C4 - Homogeneous second-order linear ODE (ver. 49)

Find the general solution to the given ODE.

$y''+6y'+9y = 0$

$y= k_{1} t e^{\left(-3 \, t\right)} + k_{2} e^{\left(-3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 50)

Find the general solution to the given ODE.

$y''+6y'+9y = 0$

$y= k_{1} t e^{\left(-3 \, t\right)} + k_{2} e^{\left(-3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 51)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 52)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 53)

Find the general solution to the given ODE.

$y''-8y'+16y = 0$

$y= k_{1} t e^{\left(4 \, t\right)} + k_{2} e^{\left(4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 54)

Find the general solution to the given ODE.

$y''-8y'+16y = 0$

$y= k_{1} t e^{\left(4 \, t\right)} + k_{2} e^{\left(4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 55)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 56)

Find the general solution to the given ODE.

$y''+6y'+9y = 0$

$y= k_{1} t e^{\left(-3 \, t\right)} + k_{2} e^{\left(-3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 57)

Find the general solution to the given ODE.

$y''+8y'+16y = 0$

$y= k_{1} t e^{\left(-4 \, t\right)} + k_{2} e^{\left(-4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 58)

Find the general solution to the given ODE.

$y''+8y'+16y = 0$

$y= k_{1} t e^{\left(-4 \, t\right)} + k_{2} e^{\left(-4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 59)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 60)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 61)

Find the general solution to the given ODE.

$y''-2y'+y = 0$

$y= k_{1} t e^{t} + k_{2} e^{t}$

## C4 - Homogeneous second-order linear ODE (ver. 62)

Find the general solution to the given ODE.

$y''+2y'+y = 0$

$y= k_{1} t e^{\left(-t\right)} + k_{2} e^{\left(-t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 63)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 64)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 65)

Find the general solution to the given ODE.

$y''+8y'+16y = 0$

$y= k_{1} t e^{\left(-4 \, t\right)} + k_{2} e^{\left(-4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 66)

Find the general solution to the given ODE.

$y''+6y'+9y = 0$

$y= k_{1} t e^{\left(-3 \, t\right)} + k_{2} e^{\left(-3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 67)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 68)

Find the general solution to the given ODE.

$y''-2y'+y = 0$

$y= k_{1} t e^{t} + k_{2} e^{t}$

## C4 - Homogeneous second-order linear ODE (ver. 69)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 70)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 71)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 72)

Find the general solution to the given ODE.

$y''-8y'+16y = 0$

$y= k_{1} t e^{\left(4 \, t\right)} + k_{2} e^{\left(4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 73)

Find the general solution to the given ODE.

$y''-8y'+16y = 0$

$y= k_{1} t e^{\left(4 \, t\right)} + k_{2} e^{\left(4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 74)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 75)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 76)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 77)

Find the general solution to the given ODE.

$y''-10y'+25y = 0$

$y= k_{1} t e^{\left(5 \, t\right)} + k_{2} e^{\left(5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 78)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 79)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 80)

Find the general solution to the given ODE.

$y''-8y'+16y = 0$

$y= k_{1} t e^{\left(4 \, t\right)} + k_{2} e^{\left(4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 81)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 82)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 83)

Find the general solution to the given ODE.

$y''+2y'+y = 0$

$y= k_{1} t e^{\left(-t\right)} + k_{2} e^{\left(-t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 84)

Find the general solution to the given ODE.

$y''+8y'+16y = 0$

$y= k_{1} t e^{\left(-4 \, t\right)} + k_{2} e^{\left(-4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 85)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 86)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 87)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 88)

Find the general solution to the given ODE.

$y''+8y'+16y = 0$

$y= k_{1} t e^{\left(-4 \, t\right)} + k_{2} e^{\left(-4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 89)

Find the general solution to the given ODE.

$y''+10y'+25y = 0$

$y= k_{1} t e^{\left(-5 \, t\right)} + k_{2} e^{\left(-5 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 90)

Find the general solution to the given ODE.

$y''-6y'+9y = 0$

$y= k_{1} t e^{\left(3 \, t\right)} + k_{2} e^{\left(3 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 91)

Find the general solution to the given ODE.

$y''+8y'+16y = 0$

$y= k_{1} t e^{\left(-4 \, t\right)} + k_{2} e^{\left(-4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 92)

Find the general solution to the given ODE.

$y''-2y'+y = 0$

$y= k_{1} t e^{t} + k_{2} e^{t}$

## C4 - Homogeneous second-order linear ODE (ver. 93)

Find the general solution to the given ODE.

$y''-2y'+y = 0$

$y= k_{1} t e^{t} + k_{2} e^{t}$

## C4 - Homogeneous second-order linear ODE (ver. 94)

Find the general solution to the given ODE.

$y''+8y'+16y = 0$

$y= k_{1} t e^{\left(-4 \, t\right)} + k_{2} e^{\left(-4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 95)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 96)

Find the general solution to the given ODE.

$y''-8y'+16y = 0$

$y= k_{1} t e^{\left(4 \, t\right)} + k_{2} e^{\left(4 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 97)

Find the general solution to the given ODE.

$y''+2y'+y = 0$

$y= k_{1} t e^{\left(-t\right)} + k_{2} e^{\left(-t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 98)

Find the general solution to the given ODE.

$y''+4y'+4y = 0$

$y= k_{1} t e^{\left(-2 \, t\right)} + k_{2} e^{\left(-2 \, t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 99)

Find the general solution to the given ODE.

$y''+2y'+y = 0$

$y= k_{1} t e^{\left(-t\right)} + k_{2} e^{\left(-t\right)}$

## C4 - Homogeneous second-order linear ODE (ver. 100)

Find the general solution to the given ODE.

$y''-4y'+4y = 0$

$y= k_{1} t e^{\left(2 \, t\right)} + k_{2} e^{\left(2 \, t\right)}$